Querying the Causal Role of Attitudes in Educational Attainment. (5th November 2012) - Gorard, Stephen
Abstract : This paper synthesizes the evidence on the causal impact of attitudes on educational attainment using a simple four-element model of causation—requiring association, sequence, intervention, and explanation. Overall, there was no clear evidence that intervening to change the educational attitudes of disadvantaged students will lead to enhanced attainment. Some mental concepts, such as external motivation, show promise and could be developed further. Others, like locus of control, show little promise and could even be dangerous if used without care. Given that there are other approaches that can help to overcome the poverty gradient in schools, raising aspirations is not the way for policy to go. The stratification of educational outcomes is more likely to be structural rather than mental. An improved attitude without the competence to do something about it could be ineffective, whereas competence may be sufficient in isolation. The current evidence is that attitudes do not cause variation in attainment, and so policies and practices based on a belief that they do are being, and will continue to be, ineffective. Such policies also present opportunity costs, using budget that could be used for more promising approaches, and leaving the poverty gradient largely untouched for yet another generation.